Daśavidharāga navati kusuma mañjari : saṅgita sāhitya prabandhamu - Narayana Das, Azzada Adibhatla, 1864-1945 (Narayana Das, Azzada Adibhatla, 1864-1945. Works. 1977 ;, 1977)
Songs in praise of Parvati, Hindu deity; lyrics written for one hundred and eighty already existing melodies (ragas) in Karnatic music.